2020
DOI: 10.1080/13617672.2020.1782612
|View full text |Cite
|
Sign up to set email alerts
|

Religious identity commitments of emerging adults raised in strictly Reformed contexts in the Netherlands

Abstract: This qualitative study examines the religious identity commitments of 18 emerging adults who grew up in strictly Reformed contexts in the Netherlands. During in-depth narrative interviews with photo elicitation, the participants reflected on who they are and the meaning of religion to their identity. Our thematic data analysis reveals that the participants' religious identity commitments are diverse and diffuse, although they all were religiously socialised in more or less the same way. It, therefore, is inade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This nding looks similar to Visser-Vogel (2015), who found three important themes in a study of Muslim adolescents in the Netherlands: acquiring knowledge (conceptual component), participating in and being involved with their own communities (collective component), and following the commandments of Allah (practical component). These components also appear by de Bruin-Wassinkmaat et al (2021) in the context of religious identity commitment.…”
Section: Discussionmentioning
confidence: 94%
“…This nding looks similar to Visser-Vogel (2015), who found three important themes in a study of Muslim adolescents in the Netherlands: acquiring knowledge (conceptual component), participating in and being involved with their own communities (collective component), and following the commandments of Allah (practical component). These components also appear by de Bruin-Wassinkmaat et al (2021) in the context of religious identity commitment.…”
Section: Discussionmentioning
confidence: 94%
“…Prior studies have emphasised that religion is essential for the establishment of sameness and coherence in the development of individuals’ identities (Erikson, 1968). Thus, as de Bruin-Wassinkmaat et al (2020) suggested, RC is fundamental for the promotion of a coherent identity, a positive recognition of the self, and others, and helps people to better understand the purpose of life, a question which often arises during adolescence. Despite this post-modern subjectivism, in which the norm seems to be non-commitment and openness to everything, young people strive to identify who they are and find a purpose and meaning in their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Commitment takes place when an adolescent is dedicated to a choice regarding identity matters (Erikson, 1968). For Erikson, religion can make an important contribution to identity (De Bruin‐Wassinkmaat et al, 2020). Balkin et al define religious identity as a ‘process in which individuals explore and commit to a set of religious beliefs and/or practices’ (Balkin et al, 2009, p. 420).…”
Section: Introductionmentioning
confidence: 99%